Lithium supplement agent and preparation method thereof, positive plate, battery, battery pack and electric equipment
By forming a first cladding layer composed of carbon material and metal single atoms on the surface of the lithium supplement material of the positive electrode lithium supplement material, the existing lithium supplement agent has solved the problems of high decomposition voltage, poor conductivity and easy water absorption, and the effect of improving the battery circulation performance is achieved.
Patent Information
- Application Number
- CN202411765835.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing positive electrode lithium supplement agents have problems such as high decomposition voltage, poor conductivity, and easy water absorption, resulting in low gram capacity of the positive electrode active material, thereby reducing the cycling performance of the battery.
A lithium supplement agent is used that includes a lithium supplement material and a first cladding layer present on the surface of the lithium supplement material. The first cladding layer consists of a carbon material and a metal single atom supported on the carbon material. The metal single atom can act as a catalyst to reduce the decomposition voltage, while the carbon material improves conductivity and prevents hydrolysis.
The decomposition voltage of lithium supplement material is reduced, the conductivity and chemical stability are improved, thereby enhancing the gram capacity of the positive electrode active material and improving the cycling performance of the battery.
Smart Images

Figure CN119786603A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a lithium supplement and a preparation method thereof, a positive electrode sheet, a battery, a battery pack and electrical equipment. Background Art
[0002] Lithium-ion batteries have the advantages of high voltage, high specific energy and environmental friendliness, and have become one of the most important energy storage technologies. However, due to the formation of SEI film on the negative electrode of lithium-ion batteries, a large amount of active lithium from the positive electrode is consumed, resulting in a decrease in the energy density and cycle performance of lithium-ion batteries.
[0003] Lithium replenishment technology, as the commanding height of the current industry competition, can not only provide additional energy density for batteries, but also greatly increase the battery cycle life. Among them, positive electrode lithium replenishers have gradually attracted people's attention due to their relatively stable, easy to synthesize, low price and high lithium replenishment capacity.
[0004] However, in the prior art, positive electrode lithium supplements have the problems of high decomposition voltage, poor conductivity, and easy water absorption, which leads to low gram capacity of positive electrode active materials. Therefore, it is urgent to develop a lithium supplement with low decomposition voltage, good conductivity, and low water absorption, so as to increase the gram capacity of positive electrode active materials. Summary of the invention
[0005] The main purpose of the present invention is to provide a lithium supplement agent, which has a low decomposition voltage, good conductivity and is not easy to absorb water, and can increase the gram capacity of the positive electrode active material, thereby improving the cycle performance of the battery.
[0006] The present invention also provides a method for preparing a lithium supplement, which can prepare the lithium supplement, has a simple process and low cost.
[0007] The present invention also provides a positive electrode sheet, comprising the above-mentioned lithium supplement agent. Therefore, when the positive electrode sheet is applied to a battery, the battery can have good cycle performance.
[0008] The present invention also provides a battery, comprising the positive electrode sheet, so the battery has good cycle performance.
[0009] The present invention also provides a battery pack, comprising the battery, so the battery pack has good cycle performance.
[0010] The present invention also provides an electrical device, comprising the above-mentioned battery or battery pack, so that the performance of the battery related to the electrical device is relatively excellent.
[0011] In a first aspect, the present invention provides a lithium supplement agent, comprising a lithium supplement material and a first coating layer present on at least a portion of the surface of the lithium supplement material; the first coating layer comprises a carbon material and metal single atoms supported on the carbon material.
[0012] The lithium supplement material as described above includes a chemical formula of Li x M y A z At least one of the materials of , wherein 2≤x≤8, 0≤y≤4, 1≤z≤6, M is selected from at least one of C, N, Fe, Ni, Co, and Mn, and A is selected from at least one of O, N, and S;
[0013] The median particle size D50 of the lithium supplement material is 50nm~500μm.
[0014] In the lithium supplement as described above, the metal single atom comprises a transition metal single atom.
[0015] The lithium supplement as described above, wherein the transition metal single atom comprises at least one of Co, Zn, Fe, Ni, and Pt;
[0016] And / or, the carbon material includes carbon nanotubes.
[0017] In the lithium supplement as described above, the density of the metal single atoms in the first coating layer is 0.1 atom / nm 2 ~100atom / nm 2 .
[0018] In the lithium supplement agent as described above, the thickness of the first coating layer is 10 nm to 10 μm.
[0019] In a second aspect, the present invention provides a method for preparing the lithium supplement as described above, comprising the following steps:
[0020] 1) Solvent thermal treatment is performed on a system including a lithium replenishing material, a metal single atom source, and a carbon source to obtain a lithium replenishing agent precursor;
[0021] 2) Under an inert atmosphere, sintering the lithium supplement agent precursor to obtain the lithium supplement agent.
[0022] In the preparation method as described above, the molar ratio of the lithium supplement material to the metal single atom source is (0.1-10):1;
[0023] And / or, the molar ratio of the metal single atom source to the carbon source is (0.1-20):1;
[0024] And / or, the temperature of the solvent thermal treatment is 50°C to 220°C, and the time is 3h to 48h;
[0025] And / or, the sintering temperature is 600° C. to 900° C.;
[0026] And / or, the metal single atom source includes a transition metal inorganic salt and / or a transition metal organic salt; the transition metal inorganic salt includes at least one of a transition metal-containing carbonate, a transition metal-containing sulfate, and a transition metal-containing nitrate; the transition metal organic salt includes at least one of a transition metal-containing acetate, a transition metal-containing carboxylate, a transition metal-containing alkyl salt, and a transition metal-containing pyridinium salt.
[0027] According to the preparation method described above, the lithium supplement agent precursor includes a lithium supplement material and a second coating layer present on at least a portion of the surface of the lithium supplement material, the second coating layer includes a metal organic framework material formed by the metal single atom source and the carbon source, and the metal organic framework material includes at least one of MOFs, ZIFs, MIL, PCN, and UIO.
[0028] In a third aspect, the present invention provides a positive electrode sheet, comprising the lithium supplement agent as described above or the lithium supplement agent prepared by the preparation method as described above.
[0029] In a fourth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0030] In a fifth aspect, the present invention provides a battery pack comprising the battery as described above.
[0031] In a sixth aspect, the present invention provides an electrical device, comprising the battery as described above or the battery pack as described above.
[0032] The lithium supplement agent provided by the present invention has a first coating layer on the surface of the lithium supplement material, and the first coating layer includes a carbon material and metal atoms loaded on the carbon material, wherein the metal atoms can play a catalytic role to reduce the decomposition voltage of the lithium supplement material, and the first coating layer includes the carbon material, which can protect the lithium supplement material from being hydrolyzed and also make the lithium supplement agent have higher conductivity, thereby increasing the gram capacity of the positive electrode active material and further improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 This is a schematic diagram of a lithium supplement provided by the present invention.
[0035] Description of reference numerals:
[0036] 101 - lithium supplementing material; 102 - first coating layer; 103 - carbon material; 104 - metal single atom. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In related technologies, lithium supplements can increase the cycle life of batteries. Different from negative electrode pre-lithiation, positive electrode pre-lithiation mostly uses indirect doping of mixed lithium supplements into the material system, or uses a lithium-rich positive electrode, which is more compatible with existing lithium battery manufacturing processes.
[0039] Although the chemical stability of positive electrode lithium replenishers is higher than that of negative electrode lithium replenishers and their advantages are more obvious, there are still some problems. For example, the existing positive electrode lithium replenishers have poor conductivity, are easy to absorb water, and have incomplete pre-lithium efficiency. Gas may be produced during the decomposition process, or because of the high decomposition energy barrier, a higher voltage is required for complete decomposition, or there are still residual low-capacity substances after the active lithium in the lithium replenisher is released, which has limited improvement on the initial charge and discharge efficiency, and often increases the impedance of the positive electrode material and reduces the specific capacity of the positive electrode material.
[0040] Based on this, in the first aspect, the present invention provides a lithium supplement, such as Figure 1 As shown, it includes a lithium supplement material 101 and a first coating layer 102 existing on at least a portion of the surface of the lithium supplement material 101 ; the first coating layer 102 includes a carbon material 103 and metal single atoms 104 supported on the carbon material 103 .
[0041] The lithium supplement agent provided by the present invention has a first coating layer on the surface of the lithium supplement material, and the first coating layer includes a carbon material and metal single atoms loaded on the carbon material, which can reduce the decomposition voltage of the lithium supplement material, improve the conductivity of the lithium supplement material, and protect the lithium supplement material from being hydrolyzed, thereby increasing the gram capacity of the positive electrode active material, and further improving the cycle performance of the battery.
[0042] The first coating layer in the present invention includes metal single atoms, because metal single atoms have extremely high catalytic activity, can provide additional active sites, promote the electrochemical reaction, so that the lithium supplement material can stably release lithium ions at a lower voltage, which helps to efficiently compensate for the loss of lithium during the battery charging and discharging process, so that the decomposition voltage of the lithium supplement material can be reduced, and the battery process problem can be solved. On the other hand, carbon materials are usually hydrophobic, so that the lithium supplement material is not easy to absorb moisture in the environment. The first coating layer can be used as a surface hydrophobic layer to block moisture and prevent moisture from corroding the lithium supplement material, protect the lithium supplement material from being hydrolyzed, improve the chemical stability of the lithium supplement material, and help to improve the cycle life of the battery. At the same time, since the carbon material itself has excellent electrical conductivity, as the main component of the first coating layer, the carbon material can make up for the problem of insufficient electrical conductivity of the lithium supplement material and improve the electrical conductivity of the lithium supplement material. This high conductivity can make lithium ions quickly transported and evenly distributed inside the lithium supplement material, thereby improving the battery charging and discharging efficiency and cycle performance.
[0043] Therefore, the lithium supplement agent provided by the present invention has a first coating layer on the surface of the lithium supplement material, and the first coating layer includes a carbon material and metal atoms loaded on the carbon material, wherein the metal atoms can play a catalytic role to reduce the decomposition voltage of the lithium supplement material, and the first coating layer includes the carbon material, which can protect the lithium supplement material from being hydrolyzed and also make the lithium supplement agent have a higher conductivity, thereby increasing the gram capacity of the positive electrode active material and further improving the cycle performance of the battery.
[0044] In some embodiments of the present invention, the lithium supplement material includes a chemical formula of Li x M y A z at least one of the materials, wherein 2≤x≤8, for example, x can be 2, 3, 4, 5, 6, 7, 8 or a range consisting of any two thereof, 0≤y≤4, for example, y can be 0, 1, 2, 3, 4 or a range consisting of any two thereof, 1≤z≤6, for example, z can be 1, 2, 3, 4, 5, 6 or a range consisting of any two thereof, M is selected from at least one of C, N, Fe, Ni, Co, and Mn, and A is selected from at least one of O, N, and S.
[0045] The median particle size D50 of the lithium supplement material is 50 nm to 500 μm, for example, it can be 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm or a range consisting of any two of them.
[0046] The lithium supplement material in the present invention may be a material having a chemical formula of Li x M y A zThe lithium supplement material can be any single material of the materials, or a composite material of two or more of the above materials. Due to different synthesis methods, the median particle size D50 of the lithium supplement material can be any size between 50nm~500μm, and can be a uniform size or a mixed material of large and small particles of different sizes. When large and small particles are mixed, they can be a single material with different sizes or a composite material with different sizes. The median particle size D50 of each material can be between 50nm~500μm.
[0047] The lithium supplement material in the present invention can provide an additional lithium source to compensate for the lithium loss caused by the decomposition of the electrolyte and the formation of the solid electrolyte interface (SEI) film, thereby improving the cycle performance and stability of the battery. The median particle size D50 of the lithium supplement material is within the above range, which is conducive to the coating of the lithium supplement material by the first coating layer, so that the lithium supplement agent formed after coating has good stability and conductivity.
[0048] In some embodiments of the present invention, the metal single atom comprises a transition metal single atom. Further, the transition metal single atom comprises at least one of Co, Zn, Fe, Ni, and Pt.
[0049] In some embodiments, the carbon material includes carbon nanotubes.
[0050] The metal single atoms in the present invention include transition metal single atoms. Transition metal single atoms (including at least one of Co, Zn, and Fe) can provide highly dispersed active sites. This metal single atom dispersion state can maximize the utilization of the metal, further promote the electrochemical reaction, and reduce the decomposition voltage of the lithium supplement material.
[0051] The excellent conductivity of carbon nanotubes can further improve the conductivity of lithium supplement materials, which is beneficial to improving the overall electron transmission capacity of lithium supplement materials, thereby improving the battery charging and discharging efficiency and cycle performance.
[0052] In some embodiments of the present invention, the density of metal single atoms in the first coating layer is 0.1 atom / nm 2 ~100atom / nm 2 , for example, it can be 0.1atom / nm 2 , 1atom / nm 2 , 5atom / nm 2 、10atom / nm 2 、30atom / nm 2 、50atom / nm 2 、70atom / nm 2 、100atom / nm 2 Or a range consisting of any two of them.
[0053] In the present invention, the density of metal single atoms in the first coating layer is within the above range, which can ensure that the metal single atoms can reduce the decomposition voltage of the lithium supplement material through their catalytic effect, and can also maximize the utilization rate of the metal single atoms and prevent the agglomeration of the metal single atoms, which is beneficial to improving the stability of the first coating layer.
[0054] In some embodiments of the present invention, the thickness of the first coating layer is 10 nm to 10 μm, for example, it can be 10 nm, 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 3 μm, 5 μm, 7 μm, 10 μm or a range consisting of any two thereof.
[0055] The thickness of the first coating layer in the present invention is within the above range, which can effectively protect the lithium supplement material from the influence of the external environment and protect the lithium supplement material from being hydrolyzed; it can also provide an additional electron transmission path to improve the overall conductivity of the lithium supplement material, and the first coating layer of appropriate thickness is conducive to uniform distribution of current, reducing the problem of excessive local current density, thereby improving the overall electrochemical performance of the material.
[0056] In a second aspect, the present invention provides a method for preparing the lithium supplement as described above, comprising the following steps:
[0057] 1) Solvent thermal treatment is performed on a system including a lithium replenishing material, a metal single atom source, and a carbon source to obtain a lithium replenishing agent precursor;
[0058] 2) Under an inert atmosphere, the lithium supplement agent precursor is sintered to obtain the lithium supplement agent.
[0059] The present invention can obtain the lithium supplement agent of the first aspect of the present invention by subjecting a system including a lithium supplement material, a metal single atom source and a carbon source to solvent thermal treatment and sintering treatment.
[0060] Specifically, in step 1), the lithium supplement material may include ternary lithium supplements such as Li5FeO4, Li2NiO2 and Li2C2O4, or binary lithium supplements such as Li2O, Li3N, Li2S, and other solid positive electrode lithium supplement materials. The carbon source may include 2-methylimidazole. Among them, the preparation of the lithium supplement precursor can be carried out by solvothermal method, electrochemical method, direct precipitation method, microwave promotion method, mechanochemical method, ultrasound assistance and self-assembly method, etc. The present invention uses solvothermal method for preparation. The lithium supplement material can be immersed in a solvent including a metal single atom source and a carbon source. Because the surface activity of the lithium supplement material is large, the metal single atom source and the carbon source are easily adsorbed and cross-linked on the surface of the lithium supplement material, so that the metal atoms in the metal single atom source and the ligands in the carbon source are coordinated, thereby forming a metal organic framework material coating layer on the surface of the lithium supplement material, that is, the coating layer of the lithium supplement precursor is a metal organic framework material.
[0061] In step 2), the lithium supplement agent precursor is sintered in an inert atmosphere to carbonize the metal organic framework material to obtain a first coating layer with high conductivity, and the first coating layer includes a carbon material and a metal single atom loaded on the carbon material, wherein the metal single atom can act as a catalyst to reduce the decomposition potential of the lithium supplement material, and the carbon material can play a role in preventing water vapor from corroding the lithium supplement agent and can improve the conductivity of the lithium supplement material. The number of sintering treatments can be determined according to the specific type of metal single atom. For example, if the metal single atom is cobalt, only one sintering treatment is performed; if the metal single atom is zinc, after one sintering treatment, the material can be hydrothermally treated to wash away excess zinc elements, and then a second sintering treatment is performed.
[0062] The preparation method of the lithium supplement provided by the present invention can prepare the lithium supplement provided by the first aspect of the present invention, and the lithium supplement can reduce the decomposition voltage of the lithium supplement material, protect the lithium supplement material from being hydrolyzed, and also make the lithium supplement agent have higher conductivity, thereby increasing the gram capacity of the positive electrode active material, and further improving the cycle performance of the battery.
[0063] In some embodiments of the present invention, the molar ratio of the lithium supplement material to the metal single atom source is (0.1-10):1, for example, it can be 0.1:1, 1:1, 3:1, 5:1, 7:1, 10:1 or a range consisting of any two of them.
[0064] In some embodiments, the molar ratio of the metal single atom source to the carbon source is (0.1-20):1, which can be 0.1:1, 0.1:1, 1:1, 3:1, 5:1, 10:1, 15:1, 20:1 or a range consisting of any two of them.
[0065] In some embodiments, the temperature of the solvent thermal treatment is 50°C to 220°C, for example, 50°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, or any two thereof. The time is 3h to 48h, for example, 3h, 10h, 20h, 30h, 40h, 48h, or any two thereof.
[0066] In some embodiments, the sintering temperature is 600° C. to 900° C., for example, 600° C., 700° C., 750° C., 800° C., 900° C. or a range consisting of any two thereof.
[0067] In some embodiments, the metal single atom source includes a transition metal inorganic salt and / or a transition metal organic salt; the transition metal inorganic salt includes at least one of a transition metal-containing carbonate, a transition metal-containing sulfate, and a transition metal-containing nitrate; the transition metal organic salt includes at least one of a transition metal-containing acetate, a transition metal-containing carboxylate, a transition metal-containing alkyl salt, and a transition metal-containing pyridinium salt.
[0068] In the present invention, the molar ratio of the lithium supplement material to the metal single atom source and the molar ratio of the metal single atom source to the carbon source are within the above ranges, which can make the thickness of the first coating layer of the final lithium supplement and the density of the metal single atoms in the first coating layer within an appropriate range, thereby reducing the decomposition voltage of the lithium supplement material, protecting the lithium supplement material from being hydrolyzed, and improving the overall conductivity of the lithium supplement material.
[0069] The temperature and time of the solvent thermal treatment in the present invention are within the above ranges, so that the metal single atom source and the carbon source can fully react to form a metal organic framework coating layer. The temperature of the sintering treatment in the present invention is within the above range, so that the metal organic framework material can be fully carbonized to form a first coating layer with high conductivity on the surface of the lithium supplement material, wherein the first coating layer includes a carbon material and metal single atoms loaded on the carbon material, which can reduce the decomposition voltage of the lithium supplement material, protect the lithium supplement material from being hydrolyzed, and can also improve the overall conductivity of the lithium supplement material.
[0070] The metal single atom source in the present invention includes a salt containing a metal single atom element, which may be an inorganic salt or an organic salt. The metal single atom element includes a transition metal element. The metal single atom source includes a transition metal inorganic salt and / or a transition metal organic salt, and the transition metal inorganic salt and the transition metal organic salt include the above-mentioned range, which can provide metal elements for forming a metal organic framework material, so that the first coating layer in the finally obtained lithium supplement agent includes metal single atoms, thereby reducing the decomposition voltage of the lithium supplement material.
[0071] In some embodiments of the present invention, the lithium supplement agent precursor includes a lithium supplement material and a second coating layer present on at least a portion of the surface of the lithium supplement material, the second coating layer includes a metal organic framework material formed by a metal single atom source and a carbon source, and the metal organic framework material includes at least one of MOFs, ZIFs, MIL, PCN, and UIO.
[0072] The second coating layer in the lithium supplement precursor of the present invention includes a metal organic framework material formed by a metal single atom source and a carbon source, and the metal organic framework material includes at least one of MOFs, ZIFs, MIL, PCN, and UIO. The type of metal organic framework material has nothing to do with the existence form of the lithium supplement material, but is only related to the type of metal single atom source, the type of carbon source, and the conditions of the solvent thermal reaction. The metal organic framework material has a porous structure, which can enhance the contact area between the lithium supplement material and the electrolyte, which is beneficial to the improvement of the battery rate performance and the rapid diffusion of lithium ions.
[0073] In a third aspect, the present invention provides a positive electrode sheet, comprising the lithium supplement agent as described above or the lithium supplement agent prepared by the preparation method as described above.
[0074] The positive electrode sheet of the present invention can be prepared by conventional technical means in the art. Specifically, the above-mentioned lithium supplement agent, positive electrode active material, conductive agent, and binder can be uniformly dispersed in a solvent to obtain a positive electrode active layer slurry, and then the positive electrode active layer slurry is coated on at least one functional surface of the positive electrode collector. After drying, the positive electrode sheet of the present invention can be obtained.
[0075] The present invention does not particularly limit the specific types of the conductive agent and the adhesive. The conductive agent, the adhesive and other components can be selected from conventional materials in the field. For example, the conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene, and the adhesive can be selected from one or more of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-propylene rubber.
[0076] The present invention does not specifically limit the coating method, and any coating method such as gravure coating, extrusion coating, spraying, screen printing, etc. can be used to coat the positive electrode active layer slurry.
[0077] The positive electrode sheet provided by the present invention comprises the above-mentioned lithium supplement agent, so when the positive electrode sheet is applied to a battery, the battery can have good cycle performance.
[0078] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet as described above. The battery has the advantages corresponding to the positive electrode sheet described above, which will not be described in detail.
[0079] The battery of the present invention includes a separator, a negative electrode and an electrolyte in addition to a positive electrode sheet. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also be a separator conventionally used in the art, such as a PP film, a PE film, etc.
[0080] The battery of the present invention can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and then a battery cell can be obtained through a stacking or winding process, and then the above-mentioned battery can be obtained through baking, liquid injection, formation, packaging and other processes.
[0081] In a fifth aspect, the present invention provides a battery pack, comprising the battery as described above. The battery pack has the advantages corresponding to the above-mentioned positive electrode sheet, which will not be described in detail.
[0082] In a sixth aspect, the present invention provides an electrical device, comprising the battery as described above or the battery pack as described above, and the electrical device has the advantages corresponding to the above-mentioned positive electrode sheet, which will not be described in detail.
[0083] The electrical equipment of the present invention can be conventional electrical equipment in the art, such as power equipment (such as electric vehicles), electronic equipment (such as computers, mobile phones, digital cameras, printers, fax machines, etc.), wearable devices (such as watches, bracelets, VR glasses, etc.), household appliances (such as air conditioners, refrigerators, washing machines, microwave ovens, etc.), etc., without special restrictions.
[0084] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0085] Example 1
[0086] The preparation method of the lithium supplement agent of this embodiment comprises the following steps:
[0087] 1) First, Fe2O3 and Li2O powders with a molar ratio of 1:5 are fully mixed in a ball mill, and then the mixture is placed in a high-temperature autoclave, and then the high-temperature autoclave containing Fe2O3 and Li2O powders is placed in a tube furnace, heated to 600°C at 6°C / min under argon protection, and maintained at this temperature for 10 hours; after the reaction is completed, wait for the temperature to drop to room temperature, take out the material and grind it for 5 hours to obtain Li5FeO4 (LFO) material. Among them, the median particle size D50 of LFO is 10μm.
[0088] 2) Dissolve hexahydrated cobalt nitrate and 2-methylimidazole in a molar ratio of 1:1 in a certain volume of methanol solvent, stir the two solutions at room temperature for 60 minutes and mix them together to form a mixed solution. Wash the lithium supplement material LFO powder with acetone and methanol three times in turn, and soak the washed lithium supplement material LFO powder in a pre-prepared mixed solution, wherein the molar ratio of LFO and hexahydrated cobalt nitrate is 1:1. Use a solvothermal method to react at 120°C for 5 hours to obtain a lithium supplement agent precursor. Among them, the lithium supplement agent precursor includes the lithium supplement material LFO, and a second coating layer existing on the surface of the lithium supplement material, and the second coating layer includes a metal organic framework material ZIF-67 formed by hexahydrated cobalt nitrate and 2-methylimidazole. Take the lithium supplement agent precursor in the reactor out of the solution, wash it with methanol, and vacuum dry it at 60°C for 6 hours. The obtained material is sintered at 800°C for 3 hours in a nitrogen atmosphere, and then naturally cooled to room temperature to obtain a lithium supplement agent (Co-LFO). The lithium supplement agent includes a lithium supplement material LFO and a first coating layer on the surface of the lithium supplement material; the first coating layer includes carbon nanotubes and metal single atoms Co loaded on the carbon nanotubes. The density of the metal single atoms Co in the first coating layer is 10atom / nm 2 , the thickness of the first coating layer is 50nm.
[0089] Example 2
[0090] The preparation method of the lithium supplement agent of this embodiment comprises the following steps:
[0091] 1) Same as Example 1;
[0092] 2) Dissolve zinc acetate and 2-methylimidazole in a molar ratio of 1:1 in a certain volume of methanol solvent, stir the two solutions at room temperature for 60 minutes and mix them together to form a mixed solution. Wash the lithium supplement material LFO powder with acetone and methanol three times in turn, and soak the washed lithium supplement material LFO powder in a pre-prepared mixed solution, wherein the molar ratio of LFO and zinc acetate is 1:1. Use a solvent thermal method to react at 60°C for 12 hours to obtain a lithium supplement agent precursor. Among them, the lithium supplement agent precursor includes the lithium supplement material LFO, and a second coating layer existing on the surface of the lithium supplement material, and the second coating layer includes a metal organic framework material ZIF-8 formed by zinc acetate and 2-methylimidazole. After washing the lithium supplement agent precursor with methanol, vacuum drying at 80°C for 12 hours. Subsequently, the prepared solid powder is sintered at 600°C in an argon atmosphere for 5 hours, and the solid is taken out, and then the solid material is hydrothermally treated in a KOH solution for 12 hours and then washed and dried. Finally, the prepared solid material was sintered at 900℃ in an argon atmosphere for 3h, cooled to room temperature and treated with 0.1M dilute hydrochloric acid for 1h to obtain a lithium supplement (Zn-LFO). The lithium supplement includes a lithium supplement material LFO and a first coating layer on the surface of the lithium supplement material; the first coating layer includes carbon nanotubes and metal single atoms Zn loaded on the carbon nanotubes. The density of metal single atoms Zn in the first coating layer is 10atom / nm 2 , the thickness of the first coating layer is 100 nm.
[0093] Example 3
[0094] The preparation method of the lithium supplement agent in Example 3 is substantially the same as that in Example 1, except that the molar ratio of LFO to cobalt nitrate hexahydrate is changed to 10:1.
[0095] Example 4
[0096] The preparation methods of the lithium supplement in Example 4 and Example 1 are basically the same, except that the molar ratio of LFO to cobalt nitrate hexahydrate is changed to 0.1:1.
[0097] Example 5
[0098] The preparation method of the lithium supplement agent in Example 5 is basically the same as that in Example 1, except that the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is changed to 0.1:1.
[0099] Example 6
[0100] The preparation method of the lithium supplement agent in Example 6 is basically the same as that in Example 1, except that the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is changed to 20:1.
[0101] Example 7
[0102] The preparation method of the lithium supplement agent in Example 7 is basically the same as that in Example 1, except that the grinding time in step 1) is changed to 48 hours.
[0103] Example 8
[0104] The preparation methods of the lithium supplement agent in Example 8 are basically the same as those in Example 1, except that the grinding time in step 1) is changed to 0.5 h.
[0105] Example 9
[0106] The preparation method of the lithium supplement agent in Example 9 is basically the same as that in Example 1, except that the temperature of the dissolution heat treatment is changed to 220° C. and the time is changed to 3 hours.
[0107] Example 10
[0108] The preparation method of the lithium supplement agent in Example 10 is basically the same as that in Example 1, except that the temperature of the dissolution heat treatment is changed to 80° C. and the time is changed to 48 hours.
[0109] Embodiment 11
[0110] The preparation method of the lithium supplement in Example 11 is basically the same as that in Example 1, except that the metal single atom source cobalt nitrate hexahydrate is replaced by ferric sulfate.
[0111] Comparative Example 1
[0112] The lithium supplement agent in Comparative Example 1 has no first coating layer and only contains the lithium supplement material LFO.
[0113] Comparative Example 2
[0114] The preparation methods of the lithium supplement agent of Comparative Example 2 and Example 2 are basically the same, except that in step 2), finally, the prepared solid material is sintered at 1100° C. in an argon atmosphere for 3 h, cooled to room temperature, and then treated with 0.5 M dilute hydrochloric acid for 1 h to obtain a lithium supplement agent (CNT-LFO).
[0115] Test example:
[0116] 1. Median particle size D50 of lithium supplement material: The median particle size D50 of lithium supplement is tested by laser particle size analyzer.
[0117] 2. Thickness of the first coating layer: A transmission electron microscope (TEM) is used to test the thickness of the first coating layer of the lithium supplement. The lithium supplement is first dispersed in an anhydrous ethanol solution to obtain a dispersion. The dispersion is then dropped onto a copper mesh for drying and sampling. The electron beam generated by an electron gun in a high vacuum environment penetrates the sample and focuses on the image. The image on the display is observed and the built-in calibration tool is used to measure the thickness of the first coating layer. The average value is calculated after measuring multiple areas to obtain the thickness of the first coating layer.
[0118] 3. Metal single atom density: Use high-resolution transmission electron microscopy (HRTEM) to measure the number of metal single atoms per unit area in the first coating layer of the lithium supplement, and calculate the average value after measuring multiple areas to obtain the metal single atom density.
[0119] 4. Specific surface area: The specific surface area of the lithium supplement is tested using the BET static method. The lithium supplement is first placed in a special adsorption instrument sample tube and subjected to high temperature pretreatment (nitrogen blowing and baking at 200°C for 2 hours) to remove surface impurities and moisture. Subsequently, an inert gas (usually nitrogen or other adsorbents) is brought into contact with the lithium supplement at a series of known relative pressures to achieve adsorption equilibrium. The instrument measures the amount of adsorption at different relative pressures, and based on these data and the BET theory, calculates the specific surface area.
[0120] 5. Surface moisture: The moisture content of the lithium supplement in each embodiment and comparative example was tested using a Karl Fischer moisture meter.
[0121] 6. Resistivity: The resistivity of the lithium supplement of each embodiment and comparative example was tested using a FT-341 four-probe tester.
[0122] 7. Gram capacity & decomposition voltage: At 25°C and normal pressure (0.1 MPa), the lithium supplement agent, PVDF and conductive carbon black of each embodiment and comparative example were respectively stirred and mixed in N-methylpyrrolidone solvent at a mass percentage ratio of 8:1:1 to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil, and after drying and cold pressing, a positive electrode sheet including a positive electrode active layer with a thickness of 100 μm was obtained; then the positive electrode sheet was punched into a small disc with a diameter of 12 mm with a film mold, and after drying and weighing, a button battery was assembled in a glove box under Ar protective atmosphere using a 2025 button battery shell, a Li metal disc as the negative electrode, and a conventional high-voltage lithium cobalt oxide electrolyte. Charge at a constant current rate of 0.2C to 4.3V. The platform voltage at this time is the decomposition voltage of the battery. Then charge at a constant voltage of 4.3V until the current is equal to 0.05C. The charging capacity at this time is recorded as the first cycle charging capacity in grams. After that, let it stand for 5 minutes, and then discharge at a constant current rate of 0.2C to a voltage of 2.0V. The discharge capacity this time is recorded as the first cycle discharge capacity in grams of the battery.
[0123] 8. Cycle performance: At 25°C and normal pressure (0.1MPa), the lithium supplement agent, the positive electrode active material LFP (lithium iron phosphate), the conductive agent acetylene black, and the binder PVDF of each embodiment and comparative example were mixed in a mass ratio of 2.5:94.5:1:2, and the solvent NMP was added. The mixture was stirred under the action of a vacuum stirrer until the system was uniform to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet. The negative electrode is made of graphite, and the separator is polypropylene, and the electrolyte (composition is 1mol / L LiPF6, the solvent is EC / DMC / DEC=v / v / v:1 / 1 / 1) to form a full battery. At 25°C, it is charged to 3.65V at a constant current of 1C, and then charged to a current rate of 0.5C at 3.65V. Then, it is discharged to 2V at a discharge rate of 1C. This charge and discharge cycle is repeated 300 times, and the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 300th cycle are measured. 300 The capacity retention rate after 300 cycles is Q=Q 300 / Q1*100%.
[0124] Table 1
[0125]
[0126] It can be seen from Table 1 that, compared with the comparative example, the lithium supplement agent provided by the present invention has a first coating layer on the surface of the lithium supplement material, and the first coating layer includes a carbon material and metal atoms loaded on the carbon material, wherein the metal atoms can play a catalytic role to reduce the decomposition voltage of the lithium supplement material, and the first coating layer includes the carbon material, which can protect the lithium supplement material from being hydrolyzed, and can also make the lithium supplement agent have a higher conductivity, thereby increasing the gram capacity of the positive electrode active material, and further improving the cycle performance of the battery.
[0127] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that the lithium supplement provided by the present invention has a higher specific surface area, a lower decomposition voltage, a lower resistivity, is not easily hydrolyzed, and can increase the gram capacity of the positive electrode active material, thereby improving the cycle performance of the battery.
[0128] Finally, it should be noted that those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses or adaptations of the present invention, which follow the general principles of the present invention and include common knowledge or customary technical means in the art not disclosed by the present invention, are not limited to the precise structure described above and shown in the drawings, and may be modified and changed in various ways without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A lithium supplement, characterized in that: It comprises a lithium supplement material and a first coating layer existing on at least a part of the surface of the lithium supplement material; the first coating layer comprises a carbon material and metal single atoms supported on the carbon material.
2. The lithium supplement according to claim 1, characterized in that: The lithium supplement material includes a chemical formula of Li x M y A z At least one of the materials of , wherein 2≤x≤8, 0≤y≤4, 1≤z≤6, M is selected from at least one of C, N, Fe, Ni, Co, and Mn, and A is selected from at least one of O, N, and S; The median particle size D50 of the lithium supplement material is 50nm~500μm.
3. The lithium supplement according to claim 1 or 2, characterized in that: The metal single atoms include transition metal single atoms.
4. The lithium supplement according to claim 3, characterized in that: The transition metal single atom includes at least one of Co, Zn, Fe, Ni, and Pt; And / or, the carbon material includes carbon nanotubes.
5. The lithium supplement according to any one of claims 1 to 4, characterized in that: The density of the metal single atoms in the first coating layer is 0.1 atom / nm 2 ~100atom / nm 2 .
6. The lithium supplement according to any one of claims 1 to 5, characterized in that: The thickness of the first coating layer is 10 nm to 10 μm.
7. A method for preparing a lithium supplement according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Solvent thermal treatment is performed on a system including a lithium replenishing material, a metal single atom source, and a carbon source to obtain a lithium replenishing agent precursor; 2) Under an inert atmosphere, sintering the lithium supplement agent precursor to obtain the lithium supplement agent.
8. The preparation method according to claim 7, characterized in that: The molar ratio of the lithium supplement material to the metal single atom source is (0.1-10):1; And / or, the molar ratio of the metal single atom source to the carbon source is (0.1-20):1; And / or, the temperature of the solvent thermal treatment is 50°C to 220°C, and the time is 3h to 48h; And / or, the sintering temperature is 600° C. to 900° C.; And / or, the metal single atom source includes a transition metal inorganic salt and / or a transition metal organic salt; the transition metal inorganic salt includes at least one of a transition metal-containing carbonate, a transition metal-containing sulfate, and a transition metal-containing nitrate; the transition metal organic salt includes at least one of a transition metal-containing acetate, a transition metal-containing carboxylate, a transition metal-containing alkyl salt, and a transition metal-containing pyridinium salt.
9. The preparation method according to claim 7 or 8, characterized in that: The lithium supplement agent precursor includes a lithium supplement material and a second coating layer present on at least a portion of the surface of the lithium supplement material, wherein the second coating layer includes a metal organic framework material formed by the metal single atom source and the carbon source, and the metal organic framework material includes at least one of MOFs, ZIFs, MIL, PCN, and UIO.
10. A positive electrode sheet, characterized in that: The invention comprises the lithium supplement agent according to any one of claims 1 to 6 or the lithium supplement agent prepared by the preparation method according to any one of claims 7 to 9.
11. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 10.
12. A battery pack, characterized in that: Comprising the battery of claim 11.
13. An electrical equipment, characterized in that: Comprising the battery according to claim 11 or the battery pack according to claim 12.
Citation Information
Patent Citations
Lithium ion battery
CN112510247A
Positive electrode lithium supplement agent and preparation method and application thereof
CN114530634A
MOF-based monatomic lithium-supplementing composite material, preparation method thereof, positive electrode material and battery
CN114583302A
Positive electrode lithium supplement agent and preparation method and application thereof
CN115863584A
Positive electrode lithium supplementing material and preparation method and application thereof
CN116544365A
Cited By
Positive current collector and preparation method thereof, positive plate, battery, battery pack and electric device
CN121394413A
ZIF-67-derived composite lithium oxalate lithium supplement agent as well as preparation method and application thereof
CN121662996A
ZIF-8 derived carbon composite lithium ferrite lithium supplement agent as well as preparation method and application thereof
CN121672587A